2020
DOI: 10.1016/j.ijid.2020.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus compared to other relevant etiologies of acute gastroenteritis among families from a semirural county in Chile

Abstract: To determine the dynamics of norovirus disease, a major cause of acute gastroenteritis (AGE), compared to other relevant etiologies, among families living in a lower middle income area. Study design: Families with three or more members and with one or more healthy children <24 months of age were followed for 1-2 years to detect any AGE. Stool samples were tested for viral and bacterial pathogens and a questionnaire was completed for those with norovirus or rotavirus AGE. Results: Between April and June 2016, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…Several studies performed worldwide have demonstrated the same pattern of GII genotypes predominance among the norovirus infections, with GII detection rates varying between 72.1% and 94.9% [ 38 , 39 , 40 ]. In Latin American, studies performed in Chile and Bolivia detected GII percentages of 85% and 97.8%, respectively, among patients with AGE [ 6 , 41 ]. In Sergipe state, southeastern Brazil, Santos et al [ 42 ] found similar detection rates of GI (6.4%) and GII (93.6%) among outpatient children <12 years old with AGE, and other studies performed in Brazil also reported the predominance of GII compared to GI among norovirus-positive samples [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies performed worldwide have demonstrated the same pattern of GII genotypes predominance among the norovirus infections, with GII detection rates varying between 72.1% and 94.9% [ 38 , 39 , 40 ]. In Latin American, studies performed in Chile and Bolivia detected GII percentages of 85% and 97.8%, respectively, among patients with AGE [ 6 , 41 ]. In Sergipe state, southeastern Brazil, Santos et al [ 42 ] found similar detection rates of GI (6.4%) and GII (93.6%) among outpatient children <12 years old with AGE, and other studies performed in Brazil also reported the predominance of GII compared to GI among norovirus-positive samples [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the era of post-rotavirus vaccination, considerable genetic diversity among NoVs was discovered worldwide. Although the genotypes varied among studies in different areas, GII.4 was still the most common over the recent 10 years [31][32][33][34][35][36][37][38][39]. The increasing prevalence of NoV infection is also associated with the recent change in global genotype distribution such as GII.4 [11,29,31,40,41].…”
Section: The Change Of Genotypes In Taiwanmentioning
confidence: 99%
“…Selected recent publications on the genotype distribution of human NoVs in various locations and the main variants identified, focused on both sporadic episodes and outbreaks, are detailed in Table 1. These studies differed in various aspects, such as their design (prospective, sometimes population-based, vs. retrospective analysis), age of participants, sporadic cases vs. outbreak-based studies, and/or hospitalized vs. community cases [33,34,43,[48][49][50][51][52][53][54][55][56]. Although the relative prevalence of NoV genotypes varied among studies and locations, genotype GII.4 was the most common among all studies.…”
Section: Molecular Epidemiologymentioning
confidence: 99%